Family therapy for eating disorders in youth: current confusions, advances, and new directions. Issue 6 (November 2018) - Lock, James
Abstract : Purpose of review: Family interventions for eating disorders are often recommended for the treatment of children and adolescents. Treatment studies and a range of treatment guidelines now recommend family-based treatment (FBT) for adolescents with anorexia nervosa (AN) and bulimia nervosa. The current report focused on studies that have been conducted over the past 2 years, most of them aimed at augmenting or improving outcomes using a range of new family approaches or adding other forms of therapy to standard FBT. Recent findings: There is increasing confusion of what type of family therapy is supported by the evidence, including FBT, FT-AN, MFT-AN, and parent-focused therapy. Seventy-five percentages of the adolescents with anorexia nervosa studies in randomized clinical trials used manualized FBT. None of the other family therapy approaches have more than 16% of the total adolescents with anorexia nervosa studied. Thus, FBT is the only form of family therapy with a substantive evidence base. Augmentation by varying the format of family therapy may be clinically useful, but differences in outcome from standard FBT are minor. Summary: The evidence base supporting the use of family therapy for adolescent anorexia nervosa is for manualized FBT. Augmentations of FBT using different formats (e.g., parents only, family groups, addition of individual therapy) have not demonstrated substantially improved outcomes over standard FBT for anorexia nervosa.